Reviving Intracranial Angioplasty and Stenting “SAMMPRIS and beyond” - Farooq, Muhammad U.; Al-Ali, Firas; Min, Jiangyong; Gorelick, Philip B. (Frontiers in Neurology, 2014)
We review the methods and results of Stenting and Aggressive Medical Management for Preventing Recurrent Stroke (SAMMPRIS) and provide a critical review of its strengths and limitations. In SAMMPRIS, the aggressive medical treatment arm (AMT arm) did substantially better than the Wingspan Stenting plus aggressive medical management arm (WS+ arm). Complications in the first 30 days post intervention led to the disparity between treatment arms. A major contribution of SAMMPRIS was the added value that AMT and lifestyle change may provide, when compared to a precursor trial, Warfarin–Aspirin Symptomatic Intracranial Disease (WASID), designed to prevent stroke in persons with high-grade symptomatic intracranial occlusive disease, however, the results of neither of these two trials have ever been reproduced. On the other hand, we argue that technical limitations of the Wingspan stent system (WS System) and lack of an angioplasty only intervention arm may have led to a premature launch of the trial and early termination of the study. Future randomized trials with different devices and modified patient selection criteria are warranted.